(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, the influence of family upbringing in the formation of tolerance in students is theoretically fully studied. In addition, as one of the most important educational institutions in Family - human life, the important role in the formation of the personality, values and relationships of children and young people has been scientifically analyzed.